Utilizing a 5G spectrum for health care to detect the tremors and breathing activity for multiple sclerosis. Issue 10 (20th July 2018) - Haider, Daniyal; Ren, Aifeng; Fan, Dou; Zhao, Nan; Yang, Xiaodong; Tanoli, Shujaat Ali Khan; Zhang, Zhiya; Hu, Fangming; Shah, Syed Aziz; Abbasi, Qammer H.
Abstract: Utilizing fifth‐generation (5G) sensing in the health care sector with increased capacity and massive spectrum range increases the quality of health care monitoring systems. In this paper, 5G C‐band sensing operating at 4.8 GHz is used to monitor a particular body motion of multiple sclerosis patients, especially the tremors and breathing patterns. The breathing pattern obtained using 5G C‐band technology is compared with the invasive breathing sensor to monitor the subtle chest movements caused due to respiration. The 5G C‐band has a huge spectrum from 1 to 100 GHz, which enhances the capacity and performance of wireless communication by increasing the data rate from 20 Gb/s to 1 Tb/s. The system captures and monitors the wireless channel information of different body motions and efficiently identifies the tremors experienced since each body motion induces a unique imprint that is used for a particular purpose. Different machine learning algorithms such as support vector machine, k‐nearest neighbors, and random forest are used to classify the wireless channel information data obtained for various human activities. The values obtained using different machine learning algorithms for various performance metrics such as accuracy, precision, recall, specificity, Kappa, and F‐measure indicate that the proposed method can efficiently identify the particular conditions experienced by multiple sclerosis patients. Abstract : Breathing and Human Activity Monitoring MS is a demyelinating disease of the central nervous system. This disease is related to mobility impairment in which the nervous system of a person is directly affected and causes many functional disabilities with the passage of time. This research presented the affective solution of monitoring different body motions and breathing activity of an MS patient. The continuous monitoring of body motion and sleep activities is very important for an MS patient. This research shows 90% accuracy in monitoring breathing and body motions. This research fully exploits the phase and amplitude information and provides very precise and grained monitoring procedure for an MS patient.